Oscillation and Evolution of Coronal Loops in a Dynamical Solar Corona - Pascoe, David J.; Goddard, Christopher R.; Van Doorsselaere, Tom (Frontiers in Astronomy and Space Sciences, 2020)
Observations have revealed two regimes of kink oscillations of coronal loops. Large amplitude oscillations excited by impulsive energy releases such as coronal mass ejections are characterised by their strong damping by resonant absorption. Lower amplitude oscillations may also be excited and sustained by the ubiquitous motions present in the corona and so are characterised as being decayless. We perform numerical simulations to study the oscillation and evolution of coronal loops in a dynamical environment. We investigate the observational signatures of kink oscillations and the Kelvin-Helmholtz instability in terms of high-resolution seismological and spatial data analysis techniques. We find that low amplitude kink oscillations are capable of generating significant changes in the loop profile which can affect estimates of the transverse loop inhomogeneity based on seismological and forward modelling methods. The disparity between methods may be indicative of nonlinear evolution of coronal loops. The influence on forward modelling estimates could also account for previous observational evidence favouring loops having wider inhomogeneous layers.